GROWTH RESPONSE OF Hibiscus cannabinus TO THE EFFECT OF CEMENT - SAHEED, KOLAWOLE OPEYEMI; KUBILI, YUSUF; SIKIRU, BELLO MUNIR; CHUKWUDI, CHUKWUMA EMMANUEL; MOHAMMED, GANI ALHASSAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
The impact of cement dust pollution on the growth performance of Hibiscus cannabinus was investigated. The seeds of Hibiscus cannabinus were obtained from reliable source, and grown on soil contaminated with different concentrations (0%, 5%, 10% 15%, 20% and 25%) of cement. All methods followed the approaches of previous authors of related subjects. Findings revealed that the cement dust affected the time of germination, although the extent varied with concentration. There were significant variations in the plant height, leaf length, stem girth, leaf width, leaf area and the chlorophyll content among the level of treatment at 0.05 level of probability. Inhibition of H. cannabinus growth attributes (plant height, stem girth, leaf length, leaf area) was more pronounced in 25% concentration followed by 20%, 15%, 10% and 5% cement concentration as compared with the control (0%). Similarly, the number of leaves decreases as the concentration increases; hence, the effect of cement dust pollution is concentration dependent. The morphological parameters of the species studied showed that the cement dust pollution affected the structure of the plant, and significant reductions were observed as concentration increases. This study revealed that cement dust pollution had significant effect on the growth and chlorophyll content of H. cannabinus especially at higher concentration (25%).